Rentierism and its divergent paths: Bahrain and the UAE during the Arab Spring. - El Sayyad, Mostafa Ashraf (AUC Knowledge Fountain, 2017)
Gulf diversity remains an under-researched topic that is stereotyped as uniform with its monarchical or Emir system relative to its Middle Eastern counterparts. This is why this thesis is initiated out of the interest to research a region that is known for its geopolitical value worldwide. Stereotyped as a region in which citizens enjoy the wealth of their nation through distribution, the events of 2011 showed otherwise. When encouraged by Middle Eastern counterparts, uprisings in Bahrain signaled that not all of the population is at ease, and that being among the â€œoil wealthyâ€ states does not necessarily imply stability and bring about citizen satisfaction. Some citizens in Bahrain have shown that they prioritize more basic freedoms and political participation. On the other hand, citizens of the UAE have seen minimal calls for reform and change, and a fairly stable system of rule. Explaining such different paths and nuancing the over-generalizing aspects of rentierism are at the core of this thesis. The thesis adopts a socio-historic approach to show that differences in state- formation, types of elites and sectarian structure account for such divergent paths.